Structural, optical, and magnetic properties of V-doped ZnO nanoparticles and the onset of ferromagnetic order - Mrabet, S.; Ihzaz, N.; Alshammari, M.; Khlifi, N.; Ba, M.; Bessadok, M.N.; Mejri, I.H.; El Mir, L. (Journal of alloys and compounds, 2022)
Pure and vanadium (V) doped ZnO nanoparticles (NPs) were successfully synthesized via a modified sol-gel method. The wurtzite crystal structure of ZnO remained intact with the vanadium doping concentrations under the present synthesis environment as confirmed by an array of advanced analytical techniques; such as Rietveld refined X-ray diffraction (XRD) pattern, as well as bond valence sum (BVS) analysis. SEM and TEM techniques were used to examine the morphology of the samples. UV-Vis-NIR spectra showed an absorption band in the UV range with reduction in the band gap from 3.23eV to 3.20eV when V content increases. Photoluminescence (PL) shows that doping with V causes the creation of some defects in the band gap of ZnO. The energy position of the obtained PL emission introduces a blue shift when the measurement temperature increases. The M-T curve is successfully fitted using both three dimensional (3D) spin wave model and Curie-Weiss law which attests to the mixed state existence of ferromagnetic (FM) and paramagnetic (PM) phases. The electron paramagnetic resonance (EPR) analysis supports the XRD results and provides evidence of oxygen vacancies (VO). Magnetic interaction is quantitatively studied and explained by polaronic percolation of bound magnetic polarons (BMP) produced by VO defects. [Display omitted] •Pure and Vanadium (V) doped ZnO nanoparticles were successfully synthesized via a modified sol-gel method.•The crystal structure of samples was determined by Rietveld XRD method.•The size and homogeneity of the crystallites were influenced by the amount of vanadium dopant used.•The existence of Oxygen vacancies and related complex defects is verified.•Formation of Bound magnetic polarons and mixed magnetic characteristics are observed.